6-th International Spring School on Acousto-optics and Applications - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1996)
At the same place as the 5-th School in 1992 at Jurata situated on the Hel Peninsula 70 km from Gdańsk the 6th International Spring School on Acousto-optics was organized by the Institute of the Experimental Physics of the University of Gdańsk in cooperation with the Polish Acoustical Society, Committee of Acoustics of the Polish Academy of Sciences and co-sponsored by the Polish Committee for Scientific Research and by the Polish Chapter of SPIE (the International Society for Optical Engineering).